2015
DOI: 10.1111/obr.12364
|View full text |Cite
|
Sign up to set email alerts
|

Impact of food labelling systems on food choices and eating behaviours: a systematic review and meta‐analysis of randomized studies

Abstract: Food labels are considered a crucial component of strategies tackling unhealthy diets and obesity. This study aims at assessing the effectiveness of food labelling in increasing the selection of healthier products and in reducing calorie intake. In addition, this study compares the relative effectiveness of traffic light schemes, Guideline Daily Amount and other food labelling schemes. A comprehensive set of databases were searched to identify randomized studies. Studies reporting homogeneous outcomes were poo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
298
1
10

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 402 publications
(334 citation statements)
references
References 40 publications
8
298
1
10
Order By: Relevance
“…A previous study suggested that food labels can effectively be used as a means of health prevention and the awareness of food label usefulness among all consumers should be raised [15]. A systematic review and meta-analysis findings suggested that nutrition labelling may be an effective approach to empowering consumers in choosing healthier products [16]. Another study suggested that food label was not commonly used among participants with inaccurate self-perception of body weight [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study suggested that food labels can effectively be used as a means of health prevention and the awareness of food label usefulness among all consumers should be raised [15]. A systematic review and meta-analysis findings suggested that nutrition labelling may be an effective approach to empowering consumers in choosing healthier products [16]. Another study suggested that food label was not commonly used among participants with inaccurate self-perception of body weight [14].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the prevention and management strategy of obesity should be to reinforce consumers' perception and use of nutrition labeling of foods [8]. Previous studies have investigated the predictors, strategies, impacts, and effectiveness on nutrition label use [7,8,[11][12][13][14][15][16][17][18][19][20][21]. Studies on the factors associating nutrition labeling and obesity are limited.…”
Section: Introductionmentioning
confidence: 99%
“…16 Research suggests that systems aligned with these recommendations can beneficially impact the nutritional quality of consumer food purchases. 17,18 Although more research is needed comparing different labelling formats, the use of interpretive systems, such as traffic-light or starbased labelling systems, appears promising in terms of improving consumers' ability to identify nutritious products. 12,18,19 Shelf labelling research is also limited.…”
Section: Evidence Fop and Shelf Labellingmentioning
confidence: 99%
“…17,18 Although more research is needed comparing different labelling formats, the use of interpretive systems, such as traffic-light or starbased labelling systems, appears promising in terms of improving consumers' ability to identify nutritious products. 12,18,19 Shelf labelling research is also limited. However, evidence suggests that such labels may promote healthier choices, especially if they do not compete for shoppers' attention with other promotions.…”
Section: Evidence Fop and Shelf Labellingmentioning
confidence: 99%
“…our 5-a-day promotion in England). Evidence from the West Australian equivalent showed the campaign increased the mean number of fruit and vegetable servings by only 0.2 over a three year period [14]. Food labeling and nutrient lists on packaged foods are compulsory by law in the vast majority of OECD countries.…”
Section: Obesitymentioning
confidence: 99%